Sialic acid-modified solid lipid nanoparticles as vascular endothelium-targeting carriers for ischemia-reperfusion-induced acute renal injury. (1st January 2017) - Hu, Jing-Bo; Song, Gui-Ling; Liu, Di; Li, Shu-Juan; Wu, Jia-Hui; Kang, Xu-Qi; Qi, Jing; Jin, Fei-Yang; Wang, Xiao-Juan; Xu, Xiao-Ling; Ying, Xiao-Ying; Yu, Lian; et al.
Abstract: In an attempt to improve therapeutic efficacy of dexamethasone (DXM)-loaded solid lipid nanoparticles (NPs) for renal ischemia-reperfusion injury (IRI)-induced acute renal injury (AKI), sialic acid (SA) is used as a ligand to target the inflamed vascular endothelium. DXM-loaded SA-conjugated polyethylene glycol (PEG)ylated NPs (SA-NPs) are prepared via solvent diffusion method and show the good colloidal stability. SA-NPs reduce apoptotic human umbilical vein endothelial cells (HUVECs) via downregulating oxidative stress-induced Bax, upregulating Bcl-xL, and inhibiting Caspase-3 and Caspase-9 activation. Cellular uptake results suggest SA-NPs can be specifically internalized by the inflamed vascular endothelial cells (H2 O2 -pretreated HUVECs), and the mechanism is associated with the specific binding between SA and E-selectin receptor expressed on the inflamed vascular endothelial cells. Bio-distribution results further demonstrated the enhanced renal accumulation of DXM is achieved in AKI mice treated with SA-NPs, and its content is 2.70- and 5.88-fold higher than those treated with DXM and NPs at 6 h after intravenous administration, respectively. Pharmacodynamic studies demonstrate SA-NPs effectively ameliorate renal functions in AKI mice, as reflected by improved blood biochemical indexes, histopathological changes, oxidative stress levels and pro-inflammatory cytokines. Moreover, SA-NPs cause little negative effects on lymphocyte count and bone mineral density while DXM leads to severe osteoporosis. It is concluded that SA-NPs provide an efficient and targeted delivery of DXM for ischemia-reperfusion-induced injury-induced AKI, with improved therapeutic outcomes and reduced adverse effects.